SMART MOSQUE: AN IOT-BASED CONTROL SYSTEM FOR MANAGING ENERGY CONSUMPTION AND FACILITY OPERATIONS - Saptaryani, Titiek Deasy; Amir, Syafiq; Wilson, Liam (Yayasan Adra Karima Hubbi, 2025)
Public and religious facilities, like mosques, often suffer from substantial energy waste due to large physical footprints, manual control, and highly intermittent, non-linear occupancy patterns. This chronic inefficiency results in high utility bills, diverting scarce community funds away from core charitable and social welfare missions, underscoring the necessity for advanced, cost-effective automation. This study aims to design and empirically validate the “Smart Mosque Architecture,” an integrated Internet of Things (IoT) system utilizing a novel Dynamic Prayer Time-Based Control Algorithm (DPT-BCA) to proactively optimize energy consumption across lighting and HVAC systems. A quantitative, quasi-experimental time-series analysis was conducted over a six-month experimental period, comparing the system’s performance against a four-month manual control baseline. The custom low-cost system achieved a statistically significant average monthly energy reduction of 30.0% (p < 0.001), driven primarily by a 47.4% reduction in HVAC runtime. Financial analysis confirmed the system’s economic viability, yielding a simple Return on Investment (ROI) in just eighteen months. The Smart Mosque Architecture is a robust and superior predictive control solution for religious facilities. The DPT-BCA successfully maximizes energy efficiency and service quality, establishing a scalable, ethical blueprint for sustainable institutional facility management worldwide.